Mechanistic Targets and Phytochemical Strategies for Breaking the Obesity-Cancer Link - Ford, Nikki A.; Lashinger, Laura M.; Allott, Emma H.; Hursting, Stephen D. (Frontiers in Oncology, 2013)
The prevalence of obesity, an established risk and progression factor for many cancers, has increased dramatically in many countries over the past three decades. Worldwide, an estimated 600 million adults are currently obese. Thus, a better understanding of the mechanistic links between obesity and cancer is urgently needed to identify intervention targets and strategies to offset the procancer effects of obesity. This review synthesizes the evidence on key biological mechanisms underlying the obesity-cancer association, with particular emphasis on obesity-associated enhancements in growth factor signaling, inflammation, and perturbations in the tumor microenvironment. These interrelated pathways and processes that are aberrantly regulated in obese individuals represent mechanism-based targets for disrupting the obesity-cancer link using phytochemicals.